PRINSIP KEADILAN PEMBELJARAN AGAMA ISLAM (KAJIAN SURAH AN-NAHL AYAT 90) - Faisal Kamal; Ali Imron; Zahrotul Ulia (Publikasi Inspirasi Indonesia, 2026)
This research aims: 1) to know the concept of the principles of fairness in Islamic religious learning according to the Al-Quran Surah An-Nahl Verse 90, 2) to know the contents and content of Surah An-Nahl verse 90, and 3) to know the principles of justice in Islamic religious learning (Study of Surah An-Nahl Verse 90.The research uses a descriptive qualitative approach and library research. Data was collected through documentation with primary and secondary data sources in the form of a study of Surah An-Nahl Verse 90, with additional secondary sources in the form of books, journals and relevant literature. The data analysis technique used is content analysis.Based on verse 90 of surah An-Nahl, the principle of justice is the subject of this research. In this research, the Al-Qur'an, relevant tafsir books, books and scientific journals were evaluated. The research results show that the principle of justice in learning means giving rights to students proportionally according to their needs and abilities rather than just giving them the same rights. The value of justice found in Surah An-Nahl verse 90 can be seen in elements such as curriculum, interactions between teachers and students, and objective and unbiased learning evaluations. Learning that is inclusive, humanistic, and focuses on building student character can be produced by applying these principles. Therefore, this verse can function as a normative basis for building Islamic religious learning that is fair and in accordance with contemporary educational requirements.